The Effect of Good Corporate Governance Mechanism on Bankruptcy Risk with Profit Management as a Mediation Variable - Halimatussakdiah; Nadirsyah; Mulia Saputra (Lembaga Bale Literasi, 2026)
The purpose of this study is to examine the influence of audit committees, independent commissioners and institutional ownership on profit management, as well as its impact on the risk of corporate bankruptcy. This study looked at 87 non-financial companies listed on the Indonesia Stock Exchange in 2021-2024, and had 339 observations. The analysis method used in this study is path analysis with unbalanced panel data. The results of this study found that only audit committees had a negative effect on profit management, while independent commissioners and institutional ownership had no effect on profit management. Furthermore, only independent commissioners and institutional ownership have a negative effect on the risk of bankruptcy, while the audit and profit management committees have no effect on the risk of bankruptcy. Another result is that profit management is unable to mediate the influence of audit committees, independent commissioners, and institutional ownership on the risk of bankruptcy